Pengaruh Metode Pirolisis Terhadap Rendemen Arang Hayati dari Tandan Kosong Kelapa Sawit dengan Variasi Bentuk Bahan dan Sistem Pembakaran: The Effect of Pyrolysis Method on the Yield of Biochar from Empty Oil Palm Fruit Bunches with Variations in Material Form and Combustion System - Zafitra Zafitra; Riskia Trizayuni; Roy Ibrahim; Muhammad Joehari Jamili; Muhammad Amrul Khoiri; Joni Irawan; Heralda Fawrin; Yeni Etma Nazar; Panji Romadhan (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2025)
This study aimed to determine the effect of pyrolysis methods on the biochar yield from oil palm empty fruit bunches (EFB) using variations in material form and combustion systems. The research was conducted from March to May 2025 in Sorek Satu, Pelalawan Regency, Riau Province, and in the Soil Science Laboratory, Faculty of Agriculture, Riau University. The study consisted of several treatments: (1) whole EFB – external semi-vacuum combustion, (2) shredded EFB – external semi-vacuum combustion, (3) whole EFB – total internal vacuum combustion, and (4) shredded EFB – total internal vacuum combustion. Collected data from the study were analyzed using descriptive statistics. The results showed that external semivacuum pyrolysis produced a higher biochar yield compared to total internal vacuum pyrolysis, with the highest yield from whole EFB at 45.6% and shredded EFB at 32.8%. The total internal vacuum system failed to produce biochar and only resulted in dry material without undergoing carbonization. The chemical characteristics from the external semi-vacuum combustion system indicated that biochar from whole EFB had higher contents of carbon, potassium, magnesium, boron, and pH, while biochar from shredded EFB tended to have higher contents of nitrogen, calcium, and iron.